Pengabdian Masyarakat Dalam Upaya Menumbuhkan Motivasi Belajar Siswa Kelas 9 MTs Ribatul Muta’allimin Kota Pekalongan - Rahmawati, Ferida; Nurlaela, Emi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
The problem of student learning difficulties that receive less attention can affect their learning motivation. The learning process will be successful when students have the motivation to learn. The purpose of Community Service Activities is to support students by providing learning motivation, solving learning problems that are being faced. This community service activity was conducted with lectures and discussions with grade 9 students, totaling 36. The stages of activities that have been carried out include greetings, introductions, apprehensions, video playback, delivery of material, question and answer discussions, and delivery of learning motivation. Community service activities receive support from schools through activity permits, providing meeting rooms and LCDs, and managing target students. The activity was conducive. Communication was established between the speaker and the student audience of community service activities. Community service activities run concurrently, student self-reflection activities need to be held to identify student problems and find solutions to student learning problems, so that problems are resolved immediately, and learning achievement can be achieved.